To Study on Scheduled Waste Management Awareness Among Community at UTHM, Parit Raja - Muhammad Aydeed,; Ismail, Shafawi (Progress in Engineering Application and Technology, 2023)
Scheduled Waste Management issues being highlighted in a higher educational institute started more than 20 years ago in developing countries. Previous studies shown, there are many discrepancies during managing scheduled wasted especially during segregation, transportation, storage, labelling and disposal. Thus, common poor practiced being captured are contaminated containers not properly labelled, expired chemical stored incorrectly, normal wastes contaminated with scheduled waste and laboratory wastes not properly managed. Even though, various initiatives have been carried out by Environmental Unit of OSHE Department, but the non-compliance issues keep recurring year by year. Therefore, this present paper aims to examine on non-compliance practices during managing the scheduled waste and to propose recovery plans to mitigate or reduce the non-compliance issues. Thus, the outcomes of the study will help UTHM management especially OSHE department to review the existing procedures and practices toward reducing schedule waste generated at campus. Also, to conduct an awareness program to all communities regards the process of managing the schedule wastes in UTHM Parit Raja. SPSS software used for data analysis to obtain descriptive statistics of the respondents’ demographic. The results from ANOVA showed there was a statistically significant different at the p < .05 for n = 53 to demographics of Positions but depicted no significant different for Gender, Age and Educational Bcakground in their perceptions to the Scheduled Waste Management.